2009
DOI: 10.1897/08-244.1
|View full text |Cite
|
Sign up to set email alerts
|

Pea (Pisum sativum) seed production as an assay for reproductive effects due to herbicides

Abstract: Even though herbicide drift can affect plant reproduction, current plant testing protocols emphasize effects on vegetative growth. In this study, we determined whether a short-growing season plant can indicate potential effects of herbicides on seed production. Pea (Pisum sativum cv. Dakota) plants were grown in mineral soil in pots under greenhouse conditions. Plants were treated with a variety of herbicides (dicamba, clopyralid, glufosinate, glyphosate, 2-methyl-4-chlorophenoxyacetic acid, primisulfuron, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Five herbicides were tested in these studies. Three were acetolactate synthase (ALS)‐inhibiting herbicides that reduced seed production based on controlled experiments (Fletcher et al 1993, 1996; Boutin et al 2000; Kjær et al 2006; Olszyk et al 2009). Two of these were from the sulfonylurea chemical family, sulfometuron (Oust®, sulfometuron methyl, 2‐[[[[(4,6‐dimethyl‐2‐pyrimidinyl)amino]carbonyl]amino] sulfonyl]benzoic acid, E.I.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five herbicides were tested in these studies. Three were acetolactate synthase (ALS)‐inhibiting herbicides that reduced seed production based on controlled experiments (Fletcher et al 1993, 1996; Boutin et al 2000; Kjær et al 2006; Olszyk et al 2009). Two of these were from the sulfonylurea chemical family, sulfometuron (Oust®, sulfometuron methyl, 2‐[[[[(4,6‐dimethyl‐2‐pyrimidinyl)amino]carbonyl]amino] sulfonyl]benzoic acid, E.I.…”
Section: Methodsmentioning
confidence: 99%
“…The EPA, ASTM, and OECD plant toxicity tests focus on vegetative growth responses, i.e., canopy height and shoot dry weight; however, research suggests that plant reproduction can be decreased with less effect on vegetative growth or injury to plants (Olszyk et al 2009, 2010; Pfleeger et al 2008; Fletcher et al 1993, 1995, 1996). Low‐dose, high‐potency herbicides are of particular concern, especially those that inhibit the enzyme acetolactate synthase (ALS) (Fairbrother and Kapustka 2001), e.g., sulfonylureas, imidazolinones, and triazolopyrimidines (Mallory‐Smith and Retzinger 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Chem. 30,2011were an artifact of the experimental design, because plants were measured 14 d after exposure, with exposures occurring at different growth stages, i.e., tuber initiation versus tuber bulking (data not shown). The other measures were taken at the end of the experiment.…”
Section: Comparing Effects Of Low Levels Of Herbicides On Plantsmentioning
confidence: 99%
“…Growth of peas outside under conditions with higher peak temperatures resulted in plants becoming stressed and, consequently, performing poorly in terms of seed production. Peas seem particularly well suited for controlled environmental conditions and this quality, along with their short life cycle, makes peas a candidate species for a reproductive test [15,30].…”
Section: Toxicity Changes Based On Plant Developmentmentioning
confidence: 99%
“…However, use of vegetative seedlings may not correspond to reproductive responses, as shown by recent research with peas, which indicated that plant reproduction (seed production) was decreased, with less effect on vegetative growth or injury to plants [2]. Low-dose, high-potency herbicides are of particular concern, especially inhibitors of the enzyme acetolactate synthase (ALS) such as sulfonylureas and imidazolinones [3].…”
Section: Introductionmentioning
confidence: 99%